The Use of Role Play Method in Efforts to Improve Capability of Posyandu Cadres - Nurwening Tyas Wisnu (Health Notions, 2018)
Early stimulation, detection and intervention for growth and development of children is a shared responsibility of health and community officials, including cadres of posyandu (integrated service post). The research that has been done is aimed at developing Posyandu cadre, with Role Play approach based on Maternal and child book (MCH book). This study was the classroom action research. The population were posyandu cadres in Bendo Sub-district. The sample size was 33, taken by simple random sampling. Instruments used were questionnaire and observation sheet. Descriptive and multivariate analyzes were used. The 38% of posyandu cadres were of late adulthood, the majority of senior high school (52%). Knowledge before role play: majority enough (88%), after role play, good (73%). Able to measure weight: good (70%). Measuring height: good (51.5%). Ability to measure head circumference well (84.8%). Able to detect developments well 82%. Able to perform vision tests with 94% good. Able to perform hearing test well (100%). Statistical analysis was no relationship between age and education with pretest knowledge. Conclusion: it was necessary to do coaching to Posyandu cadre continuously, with the use of variation of method to make lesson easier to understand. Keywords: role play; education; children; growth; development